Implications Of The Sociological Approach In Islamic Education In Indonesia - Yeni Prihatin Miftahul jannah; Ainun Suci Qur'ani; Ummi Mufida; Imroatus Sa’adah; Zulfi Mubaraq (Universitas Muhammadiyah Jember, 2022)
The sociological approach has an important role in solving various problems faced by mankind. This study aims to: first, examine the meaning of the sociological approach, second, explain the urgency of the sociological approach in Islamic education, describe the importance of the sociological approach in Islamic education, use it as a tool to understand religion because religion was revealed for social purposes, third examine the implementation of the sociological approach in Islamic education. The method used is library research by exploring primary sources, namely books and secondary sources in the form of national and international scientific journals. The results of this study indicate that: first, Islamic Education is a perspective or paradigm contained in a field of knowledge which is then used in understanding religion, studying the reciprocal relationship between religion and society, and the urgency of the sociological approach in Islamic studies is to formulate values or rules in society, tools to understand religion, second, the urgency of the sociological approach in Islamic education is to formulate values or rules in society, tools to understand religion, and theoretically be able to provide representative formulations in the scientific world, as well as being able to understand social phenomena with regard to worship in a significant way and muamalat, and third whereas one example of the implementation of the sociological approach is evidenced by the existence of tolerance in social relations in the community.